2007
DOI: 10.1016/j.colsurfa.2006.08.001
|View full text |Cite
|
Sign up to set email alerts
|

An optimized sol–gel synthesis of stable primary equivalent silica particles

Abstract: An optimized synthesis of nanometer silica particles via hydrolysis and condensation of tetraethylorthosilicate (TEOS) is described. At the optimum experimental conditions, homogeneous and stable silica nanoparticles with mean particles size of 7.1 ± 1.9 nm were obtained. The particle size is in a good agreement with primary particles. The size, size distribution (SD) and the yield of silica were controlled by the concentration of the reactants, ammonia feed rate, temperature and mixing mode. The increase in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(80 citation statements)
references
References 18 publications
6
73
0
1
Order By: Relevance
“…An important effect on the densification processes was achieved by well particle size distribution. Nanostructure phase and a narrow size distribution aid in obtaining dense and homogeneous materials [25,26], these results are compatible with the observed FTIR data.…”
Section: Resultssupporting
confidence: 89%
“…An important effect on the densification processes was achieved by well particle size distribution. Nanostructure phase and a narrow size distribution aid in obtaining dense and homogeneous materials [25,26], these results are compatible with the observed FTIR data.…”
Section: Resultssupporting
confidence: 89%
“…It has been reported [28] that the particle sizes of TEOS silica aerogels change nonlinearly with a increase of the molar ratio of water:TEOS from 1.7:1 to 100:1 (or the concentration of water from 17M t 0.5M). Other studies [29] found that particle size decreased when the molar ratio between water and TEOS increased from 1.3:1 to 55.6:1. However, little is known about the effects of water content on pore sizes in aerogels in both TEOS based silica aerogels and MTMS based silicone aerogels.…”
Section: Molar Ratio Of Water To Mtmsmentioning
confidence: 82%
“…TEOS and ethanol were mixed and stirred for 15 min. Then, NH 3 and H 2 O were added dropwise slowly and carefully while sonication was performed for 2 h. All concentrations of the reactant were calculated based on final volume in the reaction mixture 24 . Sonication process took place in an Ultrasonic Homogenizer (Krisbow model 5510, 40 kHz).…”
Section: Synthesis Of Spherical Siomentioning
confidence: 99%
“…On the other hand, SiO 2 nanoparticle was prepared by sol-gel methods 24 . If the surface of a larger particle is covered by a layer of fine particles, a core-shell system might be resulted 22 .…”
mentioning
confidence: 99%